Encontrándonos con la academia para compartir la importancia de aplicar la ciencia en las políticas públicas - Rivas, Juan Sebastián; Ortíz, Natalia; Salas Betancourt, Daniela (CGIAR System Organization, 2023)
On April 21, the Colombia team of the CGIAR Initiative on National Policies and Strategies (NPS) received a visit from a group of students from the University of the Andes. These students are enrolled in the course “Politics and Food Policies” and visited the Palmira Campus of the Alliance of Bioversity International & CIAT. The students, representing various undergraduate and graduate fields such as medicine, political science, government and public affairs, law, international relations, ecology, economics, and industrial engineering, among others, gained insights into the significance of research and innovation in agrifood systems. They also learned how science is applied in Colombian public policy, with specific examples related to climate change and the management of pests and diseases in crops of great importance to the country.